(untitled) (MCIT: Proceedings of International scientific and practical conference, 2019)
The analysis of models of diffusion of innovations in the software market is carried out. The optimization of the model of diffusion of innovations is realized, the optimal values of the corresponding parameters are found. The influence of significant factors on the dynamics of software distribution on the market is analyzed. The peculiarities of the interaction of manufacturers and users of software in the conditions of existence of the market of illegal (pirate) copies are considered.